Implementation Of Clustering With The K-Means Algorithm Method In Hospital Grouping In West Java: Penerapan Clustering Dengan Metode Algoritma K-Means Pada Pengelompokan Rumah Sakit Di Jawa Barat - Nurhaeningsih; Denni Pratama (LPPM Institut Studi Islam Sunan Doe, 2023)
Hospitals as health service institutions must provide services to the community in the local and international scope. Based on this, in the last few decades the term accreditation has emerged to assess the quality of an organization including hospitals. The state has an obligation to meet the public's need for health services which is regulated in the 1945 Constitution of the Republic of Indonesia, as well as supporting laws and regulations, namely Law Number 25 concerning Public Services, Law Number 36 of 2009 concerning health, Law Number 44 of 2009 concerning Hospitals, and Law 37 of 2008 concerning the Ombudsman of the Republic of Indonesia. to find out about matters relating to hospital accreditation and patient safety in order to improve the quality of health services in hospitals. The research design used is data mining. With clustering algorithm. Data taken from opendata.jabarprov https://opendata.jabarprov.go.id/id/dataset/register-rumah-saki-berdasarkan-tipe-dan-class-di-jawa-barat. In data mining, the results show that hospital accreditation in Indonesia is carried out to assess hospital compliance with accreditation standards. Hospital accreditation is linked to quality assessment. However, actually the quality itself is the outcome of the accreditation implementer, while accreditation only assesses whether the service has met the standard or not without measuring the quality of the service. Hospital accreditation is an acknowledgment that has been recognized by the government for hospitals because they have met predetermined standards